Two decades of capacity building to support global malaria control and elimination: retrospective and prospective international trainings in Jiangsu Institute of Parasitic Diseases, China, 2002–2021 - Cheng Liang; Xuedan Ke; Yuanyuan Cao; Weiming Wang; Mengmeng Yang; Jie Wang; Cecilia T. Hugo; Leonard Ortega; Glenda Gonzales; Guoding Zhu; Jun Cao (Malaria Journal, 2023)
Abstract Background Malaria is still one of the major infectious diseases affecting human health, and the World Health Organization (WHO) has attached special importance to malaria-related technical training for its global elimination efforts. The Jiangsu Institute of Parasitic Diseases (JIPD), designated as a WHO Collaborating Centre for Research and Training on Malaria Elimination, has conducted numerous international malaria training programmes during the last 2 decades. Methods A retrospective analysis of international training programmes organized and facilitated by JIPD in China since 2002 was conducted. A web-based questionnaire was designed to gather respondents’ basic information, evaluation of course topics, methodology, trainers, and facilitators, course impact, and suggestions for future trainings. Individuals who participated in the training courses from 2017 to 2019 were invited to participate in this assessment. Results Since 2002, JIPD has conducted 62 malaria-related international trainings attended by 1935 participants from 85 countries, covering 73% of malaria endemic countries. Of 752 participants enrolled, 170 responded to the online survey. A majority of respondents (160/170, 94.12%) gave a high evaluation of the training, with an average score of 4.52 (5 maximum score). Also, survey respondents gave a 4.28 score on “knowledge and skills gained in the training useful for the national malaria programme”, 4.52 on “topics appropriate to their professional needs”, and 4.52 on “knowledge and skills gained in the training useful to their career”. Surveillance and response was the most important topic discussed and field visit was the most effective method of training. For future training programmes, with increasing length of training, more field visits and demonstration, improving language barrier, and sharing experience were what the respondents requested most. Conclusion JIPD, as a professional institute for malaria control, has conducted a great quantity of training in the past 20 years, providing training opportunities to both malaria and non-malaria endemic countries globally. For future training, survey respondents’ suggestions will be considered to provide a more effective capacity building activity to better contribute to global malaria elimination.